Challenges and Problems Encountered by Senior High School Out-of-Campus Students in Work Immersion Program - Anabo, Roy O.; Nebrida, Rosalia N.; Sison, Marilyn N.; Lopido, Jovie Lynn C.; Picardal, Benchel M.; Rapada, Jr., Virgilio P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study determines the challenges and problems senior high school out-of-campus work immersion students encounter in managing a work immersion program. A descriptive-correlational research design and a researcher-made survey questionnaire were utilized with 110 out-of-campus senior high school work immersion students. Data on frequency, percentage, weighted mean, rank distribution, and Pearson Product Moment Correlation (Pearson r) were analyzed. Data revealed that the profile of respondents had a greater number of female than male respondents. Regarding parents' educational attainment, more finished college level for mothers and secondary level for fathers. The family's monthly income is lower. The distance from the work immersion venue is a long travel of six kilometers and above. However, challenges encountered by out-of-campus work immersion students are slightly challenging with the grand mean ranging from 3.892 to 4.09 and SD ranging from 0.751 to 0.874. Therefore, challenges and problems encountered transform into opportunities to grow in the workplace, work immersion students develop self-discipline, good attitude, and service to work. In addition, correlational analysis between challenges and problems encountered by out-of-campus senior high school work immersion students is highly significant regarding immersion teachers, field supervisors, work ethics, and students' skills and competence. Challenges and problems encountered by out-of-campus work immersion students lead to improvement in the workforce that can create motivational, psychological, and physiological needs. Developed a positive mindset to finish their work immersion program with satisfied learning. It is highly recommended that fieldwork supervisors be competitive in skills, knowledgeable, and experts in the specific fields of specialization.